Danqi soft caspule alleviates myocardial ischemia-reperfusion injury induced cardiomyocyte apoptosis by attenuating mitochondrial fission - Ye Yang; Cuiting Lin; Yan Wang; Yu Liu; Qiuxiong Chen; Qiuxiong Chen; Shiyu Ma; Shiyu Ma; Jin Ma; Jin Ma (Frontiers in Pharmacology)
BackgroundMyocardial ischemia-reperfusion (I/R) injury which leads to continuously worsening ventricular remodeling and cardiac dysfunction in the chronic stage, is a significant contributor to the global prevalence of heart failure. Traditional Chinese herbal formulas have been shown to prevent myocardial I/R injury.MethodThis study aims to investigate whether Danqi soft caspule (DQ), a classical traditional Chinese medicine (TCM) preparation, exerted the protective effects against myocardial I/R injury and explore the potential underlying mechanisms. A rat model of myocardial I/R and a cell model of H2O2 induced oxidative stress injury were established to assess the effects of DQ on cardiac injury, cardiomyocyte apoptosis, as well as mitochondrial structure and function.ResultDQ pre-treatment reduced both the proportion of infarct area and ischemic risk area and decreased cardiomyocyte apoptosis in myocardial I/R injury rats. In H2O2 induced cells, DQ was found to reduce cell apoptosis and lower oxidative stress levels. Furthermore, DQ inhibited mitochondrial fission, prevented alterations in mitochondrial membrane potential, and suppressed Cytochrome C release from the mitochondria, thereby preventing apoptosis. DQ has protective effects against I/R induced oxidative stress injury by reducing cardiomyocyte apoptosis through inhibition mitochondrial fission. Moreover, DQ could restore mitochondrial structure and function by suppressing the phosphorylation of Ca2+/calmodulin-dependent protein kinase II (CaMKII) and dynamin-related protein 1 (Drp-1).ConclusionDQ inhibited I/R injury and cardiomyocyte apoptosis by reducing mitochondrial fission associated with suppressing the phosphorylation of CaMKII and Drp-1.